The evolution of International business 1800-1945. Volume 6 : American industry in Europe - Southard, Frank A. (Frank Allan), 1907- (London ; New York : Routledge, 2000)
American industry in Europe: external form. The extent of American industry in Europe. Why American industry migrates to Europe. Organizing and operating European subsidiaries. General problems arising out of the migration of American industry to Europe.
Keywords: Corporations; Europe; Corporations -- United States; Corporations, American -- Europe; Trusts, Industrial -- Europe